PENYUSUNAN INSTRUMEN PENILAIAN GURU-GURU IPA KABUPATEN BANYUWANGI - Maulida Fauziah, An Nuril; martini, Martini; Sabtiawan, Wahyu Budi (Universitas Negeri Surabaya, 2018)
This study aims to describe the results of the preparation of assessment instruments of science teachers Banyuwangi District. This research is a descriptive research that describes the results quantitatively and supported explanation of the data that has been obtained. The results of the study indicate that the assessment instrument is valid and feasible to be used for assessment in the learning process of the mentioned KD. The conclusions of the assessment instrument developed from the four groups are all valid and worthy of use.This study aims to describe the results of the preparation of assessment instruments of science teachers Banyuwangi District. This research is a descriptive research that describes the results quantitatively and supported explanation of the data that has been obtained. The results of the study indicate that the assessment instrument is valid and feasible to be used for assessment in the learning process of the mentioned KD. The conclusions of the assessment instrument developed from the four groups are all valid and worthy of use.